Research on range-based localisation algorithm with virtual force and time synchronisation in wireless sensor and actor networks. (2016) - Wang, Haoyun; Wang, Ke; Li, Duo; Nyalala, Innocent; Xiong, Yingjun; Xu, Huanliang
In order to solve the problem of sensor node localisation of wireless sensor and actor networks, a range-based time of arrival (TOA) localisation algorithm with virtual force and time synchronisation (TLAVFTS) in WSAN is proposed in this paper, which uses mobile actors instead of WSNs anchors, and combines TOA with virtual force on the premise of time synchronisation. When a sensor node requests for localisation, the algorithm first calculates the virtual force of actor nodes, and makes it move close to the requested sensor node, then synchronise time of entire network. Finally, three-bonier measurement method will be adopted to complete node localisation. The simulation results show that the proposed algorithm can improve the success localisation rate by up to 40% and also is superior to traditional TOA on the average localisation time, error and overhead; it can apply to real-time filed with small number of actor nodes.